Pengaruh Marketing Strategy, Service Quality Dan Customer Experience Terhadap Purchase Decisions Pada Produk Fashion Ayu Citra Fashion Store Kabupaten Jombang - Zubair, Ahmad; Mustapita, Arini Fitria; Rachmadi, Kartika Rose (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to investigate and clarify how three independent factors—marketing strategy, service quality, and customer experience—affect the dependent variable, specifically the fashion product purchase choices at Ayu Citra Fashion Store located in Jombang Regency. Employing a purposive sampling method and administering Likert-scale questionnaires, 80 respondent samples were collected for the research. IBM SPSS version 25 software was employed to apply different linear regression methods and hypothesis testing, including the F test (simultaneous test) and the T test (partial test), to analyze the collected data. The research results indicated that the three separate elements—marketing strategy, customer experience, and service quality—significantly influenced consumers' choices to purchase fashion products at Ayu Citra Fashion Store in Jombang Regency. The outcomes of partial/single tests show that customer experience greatly influences purchase decisions, service quality does not significantly affect them, and marketing strategy has a substantial effect. Keywords : Marketing Strategy, Service Quality, Customer Experience, Purchase Decisions